The Critical Analysis of Principles in the Theory of Freedom fom the View of Isaiah Berlin (With Emphasis on the Ideas of Allāma Javādi ‘Amoli) - Mahdi Naderi (‫سیاست متعالیه‏, 2021)
Using a qualitative method based on textual hermeneutics, the present study aims to answer “what are the criticisms to the principles of the theory of freedom in the view of Isiah Berlin based on the idea of Allāma Javādi ‘Amoli?” The results showed that the idea of freedom in the perspective of Isiah Berlin has a root in humanistic and pluralistic thinking and that Allāma Javādi ‘Amoli’s return point in the above criticism relies on the principle of “the recognition of origin”. Accordingly, a human as a finite being, in Takwin (creation) and Tashri’ (legislation), needs an infinite being that is God. The spread of human needs to God involves the evaluation and prioritization of values too so a human has no choice but to obey God and follow the commands and prohibitions of the religion. This issue is in contrast with humanistic and pluralistic ideas in Berlin’s view.